Biologics, Small Molecules and More in Inflammatory Bowel Disease: The Present and the Future - Manish Manrai; Atul Abhishek Jha; Saurabh Dawra; Aditya Vikram Pachisia (MDPI AG, 2024)
Inflammatory bowel disease (IBD) is a group of heterogeneous chronic inflammatory diseases of the gut presenting with intestinal and extraintestinal manifestations. Most cases fit in predominantly two types, namely, ulcerative colitis and Crohn's disease. The incidence of IBD has been increasing steadily in the past three decades. Focused research has resulted in many therapeutic options. Biologics (derived from humans or animals) and small molecules have emerged as the cornerstone in the management of IBD and have become widely available. Currently, monoclonal antibodies against tumor necrosis factor-alpha (infliximab, adalimumab, certolizumab, and golimumab), integrins (vedolizumab and natalizumab), and interleukin (IL)-12 and IL-23 antagonists (ustekinumab), along with small molecules (tofacitinib), are approved for use. This article summarizes various aspects of these drugs, like clinical pharmacology, indications for use in IBD, safety in pregnancy and lactation, and the adverse effects profile based on the studies leading to their approval. This review also focuses on the recent advances and future perspectives specific to biologics in IBD.